BUDIDAYA TANAMAN HIAS UNTUK MENINGKATKAN PENDAPATAN IBU-IBU RUMAH TANGGA GPBI ZEBULON TIANGWANGKANG BATAM - Erni Yanti Natalia; Tiurniari Purba (ASOSIASI IDEBAHASA KEPRI, 2021)
One of the ethnic groups in Batam, from the many tribes, is the sea tribe. The inhabitants of the Sea Tribe live along the edge of the coastal line known as